The preventive excavation for the expansion of the cemetery of Pieve Dugliara (PC). Preliminary report (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2023)
The paper presents the data from the preventive excavation carried out in the area adjacent to the cemetery of Pieve Dugliara (PC) in the first months of 2012. The study, while including all the structures investigated, focuses on the large pit located in the southeastern corner. It shows two main phases of utilization, dated on the basis of the few materials found: a first phase around the passage between the 6th and the 5th century B.C. and a second one referable to the Roman Republican period (early 1st century B.C.). The paper provides, through comparisons, an interpretation regarding the use of the structure in the two periods and to integrate it within the local topography.
Keywords: Pieve Dugliara; Iron Age; Republican Age; ligurian pottery; Lamboglia 2 amphora; cistern